P218 It is time to grow up: readiness is associated with better outcomes in a prospective study of pediatric transition patients with Inflammatory Bowel Disease. (30th January 2023) - Nardone, O M; Martinelli, M; De sire, R; Calabrese, G; Caiazzo, A; Fioretti, M T; Testa, A; Limansky, L; Rispo, A; Di Luna, I; Miele, E; Staiano, A; et al.
Abstract: Background: Approximately 25% of patients with inflammatory bowel disease (IBD) are diagnosed before age 20, making the transition from paediatric to adult healthcare challenging due to the high burden of these diseases at a critical time, such as adolescence. We aimed to assess patients' readiness to transition from paediatric to adult IBD services and the impact on clinical outcomes. We further investigated adherence and quality of life at 12 months post- structured transition clinic Methods: An observational, prospective study was conducted in a tertiary adult and paediatric IBD centre including adolescent aged≥17yo with a confirmed diagnosis of IBD before 16yo and in clinical remission who underwent "structured transition". We collected demographics and clinical data 12 months before and after the transition visit. At the time of recruitment patients filled out the Transition Readiness Assessment Questionnaire (TRAQ) and they were defined ready based on a mean TRAQ value ≥ 3.0. The Morisky Medication Adherence Scale (MMAS) and the Short Form Health Survey (SF36) Questionnaire were completed baseline and 12 months after transition clinic. Receiving operating characteristics (ROC) curve was used to determine cut-off values of TRAQ for predicting medication adherence.We further investigated which demographic and clinical parameters could predict medication adherence. Results: We enrolled 60 patients in clinical remission based on Crohn's Disease Activity Index (CDAI) score of 115±124 for CD and pMayo 2, 85±1, 3 for UC, who had transitioned throughout transition clinic to adult care and completed 12 months follow-up [Table1]. Overall 42 patients (70%) were considered ready for transition, with a mean TRAQ score=3, 2±0, 5. The number of outpatient visits(1, 86±0, 75vs2, 28±1, 2;p<0, 02) as well as the number of clinical relapses (0, 38±0, 4vs1, 06±0, 9;p<0, 02) and hospitalizations (0, 05±0, 1vs0, 33±0, 33;p<0, 05) at 12 months were significantly lower in ready than in not-ready patients. The quality of life did not differ pre-and 12 months post-transition clinic(p=0, 09) and between ready and not-ready patients (p=0, 71)[Table2]. Based on ROC curve a TRAQ cut-off≥3, 46 could predict medication adherence with a sensibility of 55%, specificity 86% and an AUC=0, 71(0, 57-0, 85;p=0, 008)[Fig1]. At multivariate analysis, a high mean TRAQ value was associated with medication adherence at 12 months (OR:7, 042CI:1, 68-29, 54, p=0.008) Conclusion: Patients ready for transition were more likely to have fewer outpatient visits, disease flares and hospitalizations compared to not-ready patients. The quality of life did not differ pre- and post transition and between ready and not-ready patients.TRAQ score could be a reliable tool with high specificity to predict medication adherence